Pengaruh e-Katalog Pengadaan Barang/Jasa Pemerintah dalam meningkatkan UMKM - Nadillah, Dinda Yulmi (LPPM Universitas Putera Batam, 2024)
In the current era, Indonesia's economic growth is very rapid, accompanied by the development of regional autonomy, the government's need for governance continues to increase. With increasing economic effectiveness and productivity, the needs of consumers, producers and the allocation of goods for facilities and infrastructure providing public services must be carried out through the goods and services procurement process. This procurement effort is aimed at building economic growth through the procurement of goods and services so that they become more effective and efficient. The aim of this research is to analyze the effect of implementing an e-catalog for government procurement of goods and services in an effort to improve Micro, Small and Medium Enterprises (MSME). The method used is a literature review method. The data collection technique used is literature study, namely utilizing journal articles, books, online news and websites of authorized institutions. The implementation of government procurement of goods and services using e-catalogs will be more open, transparent and efficient by reducing the process and time in procuring goods and services. Efforts to implement e-catalogs in the procurement of government goods and services are very influential for the MSME sector. The government has also encouraged the use of the e-catalog system for MSME by participating in local e-catalog products. In reality, the implementation of the e-catalog system for MSME is still lacking, as evidenced by the minimal use of the e-catalog system for government procurement of goods and services by MSME due to limited capital and information regarding the use of e-catalogs for MSME.